Design and implementation of 2 kW BLDC motor for e-scooter electric vehicle according to Indonesian bicycle conversion standards - Dwi Putranto, Rifki; Haichal Sukino, Rifansyah Fitrah (Journal Geuthee of Engineering and Energy, 2025)
The main challenge faced by many countries is the limited fossil fuels due to the dwindling supply of fuel oil. Indonesia itself faces serious problems in providing sufficient fuel, even having to import from other countries, which can have a negative impact on the energy needs of its growing population. To overcome this problem, the use of renewable energy sources is a very relevant alternative solution. Renewable energy needs to be expanded, especially with the increasing price of fuel. One of the most prominent examples is the use of electrical energy. Electric motors have become a major focus in the development of electric vehicle technology and various industrial applications. One type of electric motor that is increasingly popular is the BLDC motor. The use of inefficient BLDC motors can cause significant energy waste, one of the factors that affects the design of BLDC motors is the winding configuration. This study aims to improve the performance of the 2kW electric motor dynamo to meet government regulations on electric vehicle conversion standards. BLDC motors are vital components in various industrial and transportation applications due to their high efficiency. This study focuses on the analysis of the BLDC motor winding configuration to achieve optimal energy efficiency by developing existing products. This study conducted simulations using Ansys Motor-CAD and performance tests were carried out under various load conditions. The results of the study showed an increase in efficiency from 82% to 87% and motor torque through variations in the winding configuration was obtained from 42 Nm to 54 Nm according to the results of the traction analysis of 44 Nm. This is expected to support the development of electric vehicles such as electric scooters.